Disgust as a Disease-Avoidance Mechanism. [article]. - Oaten, Megan
Many researchers have claimed that the emotion of disgust functions to protect us from disease, Although there have been several discussions of this hypothesis, none have yet reviewed the evidence in its intirety. The authors derived 14 hypotheses from a diease-avoidance account and evaluate the evidence for each, drawing upon research on pathogen avoidance in animals and empirical research on disgust. In all but 1 case, the evidence favors a disease-avoidance account. It is suggested that disgust is evoked by objects/people that process particular types of prepared features that connote disease. Such simple disgusts are directly disease related, are acquired during childhood, and are able to contaminate other objects/people. The complex disgust, which emerge later in development, may be mediated by several emotions. In these cases, violations of social norms that may subserve a disease-avoidance function, notably relating to food and sex, act as reminders of simple disgust elicitors and thus generate disgust and motivate compliance. The authors find strong support for a disease-avoidance account and suggest that it offers a way to bridge the devide between concrete and ideational accounts of disgust.-- (from the author)